Milestone documents in world history exploring the primary sources that shaped the world - Bonhomme, Brian 1962-; Boivin, Cathleen (Schlager Group, 2010)
Key documents from all important world cultures are included, from the ancient Near East and ancient Egypt to the Greek and Roman Empires, medieval Islam, Renaissance Europe, and modern Africa and Asia. Constitutions, speeches, letters, acts, treaties, and legal cases are all covered. Among the documents included in the set are iconic legal and constitutional documents such as the Code of Hammurabi, Magna Carta, Meiji Constitution, and the Constitutive Act of the African Union; famous treatises such as the Plato's "Allegory of the Cave," the Communist Manifesto, and Osama bin Laden's Declaration of Jihad against America; important legislative acts from the Treaty of Guadalupe Hidalgo to the Treaty of Nanjing to the Treaty of Versailles; and cultural and political declarations such as Martin Luther's 95 Theses, Gandhi's "Quit India" Speech, and Nelson Mandela's Inaugural Address.--From publisher description.